The Effectiveness of Using Google Forms on Students Mathematical Problem Solving Skills in The Implementation of The Final Semester Exam at The Junior High School Level - Affandi, Nurhabibah; Assegaf, Fadillah Hakim; Assegaf, Laelasari; Pramuditya, Surya Amami (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Mathematical solving ability is the ability to solve problems related to mathematical concepts. This concept is in the form of symbols, formulas, and systematic and measurable solutions, as stated by George Polya, which has four processes, namely understanding problems, planning problem solving, implementing solutions and checking results. This research was conducted at SMPN 2 Suranenggala with a sample of 4 students in grade VIII Digital-based learning can be an alternative in delivering material and evaluating learning outcomes. The use of Google forms in schools can be one of the interactive media in learning, for example making quizzes and conducting end-of-semester exams. The final semester exam is carried out as an evaluation of learning outcomes, students who have high semester exam results have good mathematical problem-solving skills